1518Preterm birth and trajectories of cardiometabolic health measures from birth to adulthood. (2nd September 2021) - Clayton, Gemma; Howe, Laura; O'Keeffe, Linda; Lewandowski, Adam; Lawlor, Deborah; Fraser, Abigail
Abstract: Background: Preterm birth is associated with increased cardiovascular disease risk, but it is unclear when this risk emerges. We compared life course trajectories from birth to adulthood of multiple cardiometabolic health measures in adults born preterm compared with term. Methods: Multilevel models were used to compare trajectories from birth to age 25 years of BMI, fat mass, lean mass, systolic and diastolic blood pressure (BP), lipids, glucose and insulin, between participants born preterm (N = 311-560) and term (N = 5365-9262) in a contemporary UK birth cohort study. We also investigated gestational age as a continuum. Results: Systolic and diastolic BP were higher at age 7 (mean predicted differences 0.8mmHg; 95%CI -0.1, 1.7 and 0.7mmHg; 95%CI 0.03, 1.3, respectively). The difference in SBP persisted and in DBP disappeared by 25 years. Preterm participants had lower BMI between 7 and 18 years, but by age 25, there was no difference. Lean mass and fat mass (measured from age 9 only) trajectories were consistent with BMI. HDL-c was higher, and triglycerides lower at birth in those born preterm, but this difference disappeared by 25 years. No other differences were found. Conclusions: There were few, modest differences in cardiometabolic health measures during early life in those born preterm versus term. All disappeared by age 25, except SBP. Longer follow-up is needed to establish if and when trajectories diverge. Key messages: By age 25, there were no differences in measures of cardiometabolic health between people born preterm and term except for a higher SBP in those born preterm.